Does It Feel the Same? Danish and Finnish Social Science and Humanities Doctoral Students’ Academic Emotions - Anttila, Henrika; Sullanmaa, Jenni; Pyhältö, Kirsi (Frontiers in Education, 2021)
Even if pursuing a doctorate is both emotionally challenging and rewarding, empirical research focusing on doctoral students' academic emotions is limited. Therefore, in this study we have contributed to bridging the gap in the research on the doctoral experience by mapping the emotional landscape of doctoral experience. In addition, we have shed light on potential invariants and socio-cultural characteristics of the emotional landscape by doing a cross-country comparison between Danish and Finnish doctoral students. A total of 272 doctoral students (Danish: 145, Finnish: 127) from the field of humanities and social sciences responded to the Cross-cultural Doctoral Experience Survey. The data were both qualitatively and quantitatively analysed, using a mixed methods approach. The results showed that the doctoral students experienced a wide range of both positive and negative emotions embedded in various activities of the doctoral experience, including supervision, scholarly community, doctoral research, development as a scholar and structures and resources. The results revealed some associations between the emotions that were experienced as well as differences between the countries.